การแยกลิกนินออกจากน้ำดำในกระบวนการทำเยื่อกระดาษจากยูคาลิปตัส - วิชชา พิชัยณรงค์ (จุฬาลงกรณ์มหาวิทยาลัย, 2002)
The acid precipitation of lignin from Eucalyptus pulping black liquor was studied. A method of two-step precipitation was proposed in this study. Prior to lignin precipitation, the polysacharide degradation products were removed from black liquor by centrifuge after precipitation at pH 6. Then the pH of black liquor was reduced to pH 5,4,3,2 and 1, respectively, with sulfuric acid in order to precipitate lignin. The lignin fraction were characterized by GPC, [superscript 13]C-NMR and IR. The results showed that more lignin precipitate when pH was reduced. At optimum pH 3, about 93.51% of the lignin was recovered.The COD and color were reduced by 80.45% and 98.20 %, respectively. The lignin fraction had molecular average weight between 1348 1540 dalton